Synthesis, crystal structures, substitutional and comparative structural analysis of copper diphosphates LiNaCuP2O7, LiKCuP2O7 and Rb0.5Na1.5CuP2O7 - Fitouri, Ines; Boughzala, Habib (European Journal of Chemistry, 2018)
The title compounds are members of the M2O-CuO-P2O5 system (M = Li, Na, K and Rb), where the lithium, sodium, potassium, rubidium and cesium phases have already been structurally characterized. The studied diphosphates LiNaCuP2O7, LiKCuP2O7 and Rb0.5Na1.5CuP2O7 belong to a large family of materials of general formula, MM’CuP2O7 (M, M’ = Monovalent cation) where the elements M and M’ ionic radii are decisive in the structural type determination. They were synthesized by solid-state reactions. The X-ray structural analysis show that these compounds crystallize in the P21/n monoclinic lattice where the CuO5 pyramidal square are linked to nearly eclipsed P2O7 groups by corner sharing to build up corrugated layers [CuP2O7]2- extending perpendicularly to [010]. The Li+, Na+, K+ and Rb+ cations reside in the interlayer space and in cavities delimited by the anionic network. In this study, the synthesis, the structure, the powder diffraction, the infrared spectroscopy, the thermal analysis (DTA/TGA) and a structural comparison are presented. The structural models were validated by Bond Valence-Sum (BVS) and charge distribution (CHARDI) analysis.